14.5k views
0 votes
Evaluate the expression when c= -4 and y= 3 c-5y

User Geniene
by
5.6k points

1 Answer

4 votes

Answer:

-19

Explanation:

If c = -4 and y = 3, replace c and y with their corresponding values in the expression, so that the expression will look like this: (-4) - (5 * 3).

Since multiplication comes before subtraction in PEMDAS, you would multiply 5 by 3, which gets you 15.

Now the expression is (-4) - (15). Then, you do the subtraction. -4 - 15 is equal to -19.

Does that help?

User Anders Sandvig
by
5.4k points